PENGETAHUAN LOKAL TUMBUHAN OBAT MASYARAKAT DESA DOMPO-DOMPO JAYA, PULAU WAWONII - SULAWESI TENGGARA - Royyani, Mohammad Fathi; Rahayu, Mulyati (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
The ethnobotanical study of plants usage of people in the Wawonii island was conductedÃ‚Â in April until May 2006. The local knowledge of medicinal plants in Wawonii island isÃ‚Â a result from interaction people of Wawonii island. Environment, another ethnics andÃ‚Â globalization, it is as cultured processes. Data were collected on the uses of plants, andÃ‚Â more than 62 species of plants were recorded in local names. The data are discussed inÃ‚Â the contect of Wawonii island culture, tradition, and way of life. Furthurmore, plants usedÃ‚Â also show the nearness of emotional relationship between human and environment.Key words: Indigenous knowledge, medicinal plants, Wawonii ethnic, SoutheastSulawesi